Chapter Introduction - Anderson, Michael Alan (Taylor & Francis, 2022)
This study uncovers the musical foundations and performance suggestions of books of hours, guides to prayer that were the most popular and widespread books of the late Middle Ages. Exploring a variety of musical genres and sections of books of hours with musical implications, this book presents a richly textured sound world gleaned from dozens of extant manuscript sources from fifteenth-century France. It offers the first overview of the musical content of these handbooks to liturgy and devotional prayer, together with cues that show scribal awareness for the articulation of sacred plainchants. Although books of hours lack musical notation, this survey elucidates the full range of musical genres and styles suggested both within and beyond the liturgical offices prescribed in books of hours. Privileging sound and ritual enactment in the experience of the hours, the survey complements studies of visual imagery that have dominated the category. The book's interdisciplinary approach within a musical context, and beautiful full-color illustrations, will attract not only specialists in musicology, liturgy, and late medieval studies, but also those more broadly interested in the history of the book, memory, performance studies, and art history.